Screening Local Sicilian Tomato Ecotypes to Evaluate the Response of Tomato Brown Rugose Fruit Virus Infection - Caruso, A. G.; Panno, Stefano; Ragona, Arianna; Peiró, Rosa; Vetrano, Filippo; Moncada, Alessandra; Miceli, Alessandro; La Marra, Consuelo Maria; Galipienso, Luis; Rubio, Luis; Davino, Salvatore (MDPI, 2024)
Tomato is one of the most important crops worldwide, with a production of ≈190 million tons, but it is constantly threatened by several viral diseases. Tomato brown rugose fruit virus (ToBRFV), identified in 2014 on tomato plants and subsequently reported in many countries, represents one of the major threats to tomato crops, due to production losses, different transmission modes and its rapid spread. This work aimed to evaluate 37 local Sicilian tomato ecotypes against ToBRFV infection. After a preliminary screening by molecular analyses for tomato mosaic virus (ToMV) and pepino mosaic virus (PepMV), and ToBRFV detection, tomato plants were grown in a greenhouse for their morphological characterization and for evaluating resistance and tolerance to ToBRFV. Resistance and tolerance levels were estimated by mechanical inoculation with ToB SIC01/19 ToBRFV isolate in ten plants per ecotype and evaluating virus accumulation by RT-qPCR and visual observation of symptoms. All ecotypes were infected with ToBRFV, showing several symptoms with different disease severity. No tomato ecotype showed a high level of resistance, but two ecotypes, Pop27 and Pop35, showed very moderate symptoms and therefore a high tolerance. These Sicilian tomato ecotypes could be used in genetic breeding programs as parental ones to obtain cultivars tolerant to ToBRFV.